Insulin-like growth factor-1 activates AMPK to augment mitochondrial function and correct neuronal metabolism in sensory neurons in type 1 diabetes - Aghanoori, Mohamad-Reza (Mol Metab, 2018)
OBJECTIVE: Diabetic sensorimotor polyneuropathy (DSPN) affects approximately half of diabetic patients leading to significant morbidity. There is impaired neurotrophic growth factor signaling, AMP-activated protein kinase (AMPK) activity and mitochondrial function in dorsal root ganglia (DRG) of animal models of type 1 and type 2 diabetes. We hypothesized that sub-optimal insulin-like growth factor 1 (IGF-1) signaling in diabetes drives loss of AMPK activity and mitochondrial function, both contributing to development of DSPN. METHODS: Age-matched control Sprague-Dawley rats and streptozotocin (STZ)-induced type 1 diabetic rats with/without IGF-1 therapy were used for in vivo studies. For in vitro studies, DRG neurons from control and STZ-diabetic rats were cultured and treated with/without IGF-1 in the presence or absence of inhibitors or siRNAs. RESULTS: Dysregulation of mRNAs for IGF-1, AMPKα2, ATP5a1 (subunit of ATPase), and PGC-1β occurred in DRG of diabetic vs. control rats. IGF-1 up-regulated mRNA levels of these genes in cultured DRGs from control or diabetic rats. IGF-1 treatment of DRG cultures significantly (P < 0.05) increased phosphorylation of Akt, P70S6K, AMPK and acetyl-CoA carboxylase (ACC). Mitochondrial gene expression and oxygen consumption rate (spare respiratory capacity), ATP production, mtDNA/nDNA ratio and neurite outgrowth were augmented (P < 0.05). AMPK inhibitor, Compound C, or AMPKα1-specific siRNA suppressed IGF-1 elevation of mitochondrial function, mtDNA and neurite outgrowth. Diabetic rats treated with IGF-1 exhibited reversal of thermal hypoalgesia and, in a separate study, reversed the deficit in corneal nerve profiles. In diabetic rats, IGF-1 elevated the levels of AMPK and P70S6K phosphorylation, raised Complex IV-MTCO1 and Complex V-ATP5a protein expression, and restored the enzyme activities of Complex IV and I in the DRG. IGF-1 prevented TCA metabolite build-up in nerve. CONCLUSIONS: In DRG neuron cultures IGF-1 signals via AMPK to elevate mitochondrial function and drive axonal outgrowth. We propose that this signaling axis mediates IGF-1-dependent protection from distal dying-back of fibers in diabetic neuropathy.